Shaping Islamic Personality: Implementing Anti-Violence Education Strategies in a Senior High School - Sudirman,; Kasim, Amrah; Saprin,; Yuspiani,; Hasanuddin, Muhammad Irfan (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to examine the development of Islamic personality through the implementation of anti-violence education at one of state senior high schools in Palopo City. Adopting a qualitative research approach with a case study design, the study utilized data collection methods such as observations, interviews, and document analysis. The data were analyzed using a modified analytical induction technique, as well as the interactive model of data analysis developed by Miles, Huberman, and Saldana, which includes processes of data condensation, data presentation, and drawing conclusions/verification. The findings reveal that violent behavior at the school manifests in various forms, including harassment, bullying, physical assault, fighting, hazing, and extortion. Some of these behaviors serve as indicators of potential triggers for future violent incidents within the school environment. The implementation of anti-violence education strategies is carried out through structural, cultural, and theological approaches. These strategies aim to address the root causes of violence and promote a more peaceful and supportive school climate. Moreover, the study shows that the implications of these anti-violence strategies extend beyond the school to include teachers, students, their families, and the wider community, suggesting a broader impact on societal attitudes towards violence and conflict resolution. Abstrak: Penelitian ini bertujuan untuk mengkaji pengembangan kepribadian Islam melalui penerapan pendidikan anti-kekerasan di salah satu sekolah menengah atas negeri di Kota Palopo. Menggunakan pendekatan penelitian kualitatif dengan desain studi kasus, penelitian ini mengumpulkan data melalui observasi, wawancara, dan analisis dokumen. Data yang diperoleh dianalisis dengan menggunakan teknik induksi analitis yang dimodifikasi, serta model analisis data interaktif yang dikembangkan oleh Miles, Huberman, dan Saldana, yang mencakup proses kondensasi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa perilaku kekerasan di sekolah tersebut muncul dalam berbagai bentuk, termasuk pelecehan, perundungan, penyerangan fisik, perkelahian, perpeloncoan, dan pemerasan. Beberapa bentuk perilaku ini menjadi indikator potensi pemicu kekerasan yang dapat terjadi di masa depan di lingkungan sekolah. Penerapan strategi pendidikan anti-kekerasan dilakukan melalui pendekatan struktural, kultural, dan teologis. Strategi-strategi ini bertujuan untuk mengatasi akar penyebab kekerasan dan menciptakan iklim sekolah yang lebih damai dan mendukung. Selain itu, penelitian ini juga menunjukkan bahwa implikasi dari strategi anti-kekerasan ini meluas ke luar sekolah, mencakup para guru, siswa, keluarga mereka, dan masyarakat luas, yang mengindikasikan dampak yang lebih besar terhadap sikap sosial terhadap kekerasan dan penyelesaian konflik.